2018
DOI: 10.1101/373886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haplotype-phased common marmoset embryonic stem cells for genome editing using CRISPR/Cas9

Abstract: Due to anatomical and physiological similarities to humans, the common marmoset (Callithrix jacchus) is an ideal organism for the study human diseases. Researchers are currently leveraging genome-editing technologies such as CRISPR/Cas9 to genetically engineer marmosets for the in vivo biomedical modeling of human neuropsychiatric and neurodegenerative diseases. The genome characterization of these cell lines greatly reinforces these transgenic efforts. It also provides the genomic contexts required for the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The common marmoset (C. jacchus) embryonic stem cell line cj367 11,12 established at the Wisconsin National Primate Research Center (kindly provided by Dr. T. G. Golos) was cultured in E8 medium (Cat# A15169-01; Thermo Fisher Scientific, Waltham, MA), with E8 supplement (1X; Cat# A15171-01; Thermo Fisher Scientific); GlutaMAX (1X; Cat# 35050-061; Life Technologies, Grand Island, NY); lipid concentrate (1:100; Cat# 11905-031; Life Technologies); recombinant human nodal (100 ng/mL; Cat# 3218-ND; R&D Systems, Minneapolis, MN); and glutathione (1.94 μg/mL; Cat# G4251; Sigma Aldrich, St. Louis, MO). Cells were grown on matrigel-coated plates (0.083 μg/ well; Cat# 354230; BD Biosciences, San Jose, CA) and passaged using Accutase (Cat# 7920; Stem Cell Technologies, Vancouver, Canada) when reaching 80% confluency.…”
Section: Marmoset Embryonic Stem Cellsmentioning
confidence: 99%
“…The common marmoset (C. jacchus) embryonic stem cell line cj367 11,12 established at the Wisconsin National Primate Research Center (kindly provided by Dr. T. G. Golos) was cultured in E8 medium (Cat# A15169-01; Thermo Fisher Scientific, Waltham, MA), with E8 supplement (1X; Cat# A15171-01; Thermo Fisher Scientific); GlutaMAX (1X; Cat# 35050-061; Life Technologies, Grand Island, NY); lipid concentrate (1:100; Cat# 11905-031; Life Technologies); recombinant human nodal (100 ng/mL; Cat# 3218-ND; R&D Systems, Minneapolis, MN); and glutathione (1.94 μg/mL; Cat# G4251; Sigma Aldrich, St. Louis, MO). Cells were grown on matrigel-coated plates (0.083 μg/ well; Cat# 354230; BD Biosciences, San Jose, CA) and passaged using Accutase (Cat# 7920; Stem Cell Technologies, Vancouver, Canada) when reaching 80% confluency.…”
Section: Marmoset Embryonic Stem Cellsmentioning
confidence: 99%
“…The first set of eight common marmoset embryo–derived pluripotent stem cell lines were isolated in 1996 [ 38 ]. Subsequently, other research groups also established C. jacchus ESC (cjESC) cell lines [ 39 , 40 , 41 , 42 ]. Studies have shown that they can be propagated in vitro both on feeder layers and in feeder-independent culture conditions [ 43 , 44 ], and that they can be genetically modified using CRISPR/Cas9 gene editing and the PiggyBac transposase system [ 45 , 46 ].…”
Section: Marmoset Embryonic Stem Cellsmentioning
confidence: 99%